2012
DOI: 10.1016/j.ecresq.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Spanish-speaking Mexican-American families’ involvement in school-based activities and their children's literacy: The implications of having teachers who speak Spanish and English

Abstract: For a sample of low-income, Spanish-speaking Mexican-American families (n = 72), we investigated associations between family involvement in school-based activities and children’s literacy in their preferred language (English or Spanish) during early elementary school. We gave special attention to the potential moderating role of teacher fluency in Spanish. Between kindergarten and third grade, family involvement in school-based activities increased for children who displayed early literacy problems. The rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 44 publications
(58 reference statements)
1
18
0
Order By: Relevance
“…That is, the consequences of school-based involvement may be moderated by the family-school fit, which may be less than optimal for many immigrant families. Namely, the value of school-based involvement may be moderated by how welcoming the school is in emotional and practical ways (e.g., language of the teacher; Tang et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the consequences of school-based involvement may be moderated by the family-school fit, which may be less than optimal for many immigrant families. Namely, the value of school-based involvement may be moderated by how welcoming the school is in emotional and practical ways (e.g., language of the teacher; Tang et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence demonstrating a positive association between family involvement and student outcomes across ethnic groups (Fan & Chen, 2001; Jeynes, 2007). In addition, research findings suggests that subgroups with “at-risk” characteristics for academic under-achievement (e.g., children from families with low-income, low maternal education, or from homes in which English is not the first language) may benefit uniquely from involvement (Dearing, Kreider, Simpkins, & Weiss, 2006; Tang, Dearing, & Weiss, 2012). …”
Section: Family Educational Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most previous studies examining Mexican parental educational beliefs have been qualitative and have generally suggested that families on average are less involved in their children's education compared to other groups (Perry, Mitchell Kay, & Brown, 2008). In contrast to this literature is a rich body of works documenting that Mexican parents highly value education, hold a strong desire to have their children succeed academically, consider themselves active participants in their child's educational development, and when necessary adapt by adjusting to the exigencies of American school expectations (Kummerer & Lopez, Reyna, 2006;Lopez, Sanchez, & Hamilton, 2000;Reese & Gallimore, 2000;Rogoff, Moore, Correa-Chávez, & Dexter, 2015;Tang, Dearing, & Weiss 2012). For example, Reese and Gallimore (2000) found that Latino mothers in their study shared a view that situated the development of language, literacy, and reading as something learned at school, not at home, through repeated practice when a child begins formal schooling.…”
Section: Parental Literacy Beliefsmentioning
confidence: 92%
“…This study found a positive relationship between rates of school participation and teachers' fluency in Spanish. However, it did not identify why or how this language fluency might produce such a result (Tang, Dearing, & Weiss, 2012). A second small qualitative study of 21 low-income, immigrant Latino families found that mothers intentionally selected bilingual early care and education programs so that they could communicate with providers; improve their own at-home parenting skills, particularly related to behavioral challenges; and prepare for their children's transition into kindergarten.…”
mentioning
confidence: 99%